Aplicación del proceso de atención de enfermería en paciente postparto con retención placentaria en el área de emergencia del Hospital Alfredo Noboa Montenegro. - Borja Carrillo, Ingrid Janina (2020)
Placental retention is a puerperal complication, the risk of maternal morbidity and mortality is higher in indigenous women tan in no-indigenouss women, due to their own notion of health and disease, beliefs and customs. Unfortunately, indigenous women do not frequent health facilities, due to many factors: geographical location, low socieconomic status, culture of their population groups, among others. Under this premise, this clinical case study was conducted in a large multiparous patient of indigenous ethnicity in a state of gestation that culminated with preterm delivery at home plus fetal death, which kept the placenta held for 29 hours. Reason why you go to Alfredo Noboa Montenegro Hospital referred by ECU 911 staff. The management of the complication was activated quickly and efficiently in the emergency área. Inmediately, admission to the Obstetric Center was indicated where manual removal of the placenta was performed, guaranteeing the patients vitality and subsequent admission to the gynecology room for recovery. In this clinical case study, we seek to perceive the importance of the nursing care plan, focused on the Florence Nightingale model, Marjory Gordon's funtional patterns and Callista Roy's adaptation model, in order to establish the well-being and comfort of the patient and lessen the consequences such as septic shock and death.